Galectin-3 Expression in Human Endometrium and Decidua During The Menstrual Cycle and in Gestation - Nevra Dursun; Melin Özgün Geçer; Pelin Yıldız; Cem Leblebıcı; Erol Rüştü Bozkurt; Nimet Karadayı; Fadime Bahadır (Medical Network, 2011)
OBJECTIVE: G3 is one of the members of the lectin family that may be involved in the establishment of endometrial receptivity by regulating the proliferation and adhesion of endometrial cells. STUDY DESIGN: Immunohistochemical expression of G3 was tested in late secretory phase of the endometrium (SPE)(n=30), proliferative phase of the endometrium (PPE)(n=34), and decidua (n=41) and induced abortions in the first trimester. RESULTS: Expression of G3 during the PPE was low; 12 cases were score 1 and 19 cases were score 2 (p<0.001). However, among the late SPE, there were 11 cases at score 2, and 15 cases at score 3. In the decidua expression of G3, 37 cases were score 3 (p<0.001). CONCLUSION: There is a significant progression of G3 expression in SPE and gestation. Although during the PPE expression is considerably lower. This shows that G3 plays an important role in implantation.